A Novel Approach to Power Flow Analysis for Grid Connected Micro Grid - Efe, Serhat Berat; Cebeci, Mehmet; Erdogan, Huseyin; Ozturkmen, Gokmen (Ieee, 2015)
This paper proposes a neural network based power flow analysis method that applied on a grid connected and ring-shaped micro grid. As the use of micro grids increasing rapidly, it becomes necessary to analyze them for different operating and loading conditions as large power systems. At the outset, a MG is designed and simulated under MATLAB / Simulink platform. Normal operation data collected and stored. Then, different loading scenarios performed, operational data collected and stored to use for proposed method. Intelligent systems are used to process these data and also for training. After training a fully different scenario is created and the effectiveness of the proposed method is verified through simulation study. Also a fault condition analysis is performed for validity.
13th International Conference on Engineering of Modern Electric Systems (EMES) -- JUN 11-12, 2015 -- Oradea, ROMANIA
Keywords: Micro grid; power flow analysis; artificial neural networks; renewable energy sources